Cancer‐associated fibroblasts might sustain the stemness of scirrhous gastric cancer cells via transforming growth factor‐β signaling. Issue 8 (24th October 2013) - Hasegawa, Tsuyoshi; Yashiro, Masakazu; Nishii, Takafumi; Matsuoka, Junko; Fuyuhiro, Yuhiko; Morisaki, Tamami; Fukuoka, Tatsunari; Shimizu, Kiyoshi; Shimizu, Toshiyuki; Miwa, Atsushi; Hirakawa, Kosei
<x xml:space="preserve">Abstract</x> Cancer‐associated fibroblasts (CAFs) have recently been implicated in tumor growth and metastasis in gastric cancer. Cancer stem cells (CSCs) have been proposed to have an important role in cancer progression. The aim of this study was to clarify the effect of CAFs on CSCs characteristics in gastric carcinoma. Scirrhous gastric cancer cell lines, OCUM‐12 and OCUM‐2MD3, and non‐scirrhous gastric cancer cell lines, MKN‐45 and MKN‐74, were used. OCUM‐12/side population (SP) cells and OCUM‐2MD3/SP cells were sorted by flow cytometry as CSC‐rich cells from the parent cells. CaF‐37 was established from the tumoral gastric specimens as CAFs. Flow cytometric analysis of SP fraction, spheroid colony assay, and RT‐PCR analysis of CSC markers were performed to identify CSCs properties. Effect of CAFs on the tumorigenicity by OCUM‐12/SP cells was examined using nude mice. CAF CM significantly increased the percentages of the SP fraction of OCUM‐12/SP and OCUM‐2MD3/SP cells, but not that of MKN‐45/SP and MKN‐74/SP cells. Taken together, CM from CaF‐37 significantly increased the number of spheroid colonies and the expression level of CSC markers of OCUM‐12/SP and OCUM‐2MD3/SP cells. These stimulating‐activities by CM were significantly decreased by TGFβ inhibitors, but not FGFR and cMet inhibitor. Tumorigenicity by subcutaneous coinoculation of OCUM‐12/SP cells with CAFs was significantly high in comparison with that by OCUM‐12/SP cells alone. Phospho‐Smad2 expression level was significantly increased by co‐inoculation with CAFs. These findings suggested that CAFs might regulate the stemness of CSCs in scirrhous gastric cancer by TGFβ signaling.